The role of governance, financial development and globalisation nexus towards foreign direct investment inflows: a response to the level of income groups / Marhamah Mohd Rafidi - Mohd Rafidi, Marhamah (2021)
Foreign Direct Investment (FDI) is one of the most important instruments for stimulating the income of a country. High FDI Inflows facilitate good quality infrastructure, health and education systems, human development, greater job opportunities to the country. Unfortunately, the Global FDI reduced by about USD 1.75 trillion in 2016 and FDI for developing countries are severely degraded by 14 per cent. Countries with Low FDI Inflows usually experienced high unemployment rates, mass poverty, lack of capital formation, income inequality, poor education, and health systems. Prior studies have examined various factors such as market size, infrastructure, trade openness, energy use, and technology in affecting FDI Inflows. These factors identified poor ability to predict the trend and economic shocks. Previous literature portrays insufficient evidence to explain the nexus among globalization, governance, and financial development. Incorporating the Eclectic and the Institutional FDI Fitness Theory, this study aimed to examine quality of governance, political globalisation, social globalisation and financial development as the key determinants of FDI Inflows in developing countries. Subsequently, this study further analysed whether financial development has a moderating effect on the relationship between quality of governance, political globalisation, social globalisation and FDI Inflows. The data for Each of the determinants: quality of governance, financial development, political and social globalisation were collected from the International Country Risk Guide, KoF Globalisation Indexes, World Bank’s World Development Indicators from 1984 to 2016. Sample size is further divided into 19 Upper Middle-Income Countries and 23 Lower Middle-Income Countries. The study used the Cross-Sectional Autoregressive Distributed Lag (CS-ARDL) to examine the relationship between quality of governance, financial development, political and social globalization and FDI inflow in Upper and Lower Middle-Income countries. This study proposed to use the Institutional FDI Fitness and the Eclectic Theory for better identifying key determinants of FDI Inflows across developing countries. In terms of research methodology, the study developed models that reduce the issue of Cross-Sectional Dependency among sample countries. The body of knowledge related to FDI Inflows was further enhanced by integrating quality of governance, the globalization nexus and financial development in the model. The findings revealed that Political and Social Globalization is significant in fostering FDI Inflows while quality of governance and financial development opposed FDI Inflows in Upper Middle-Income countries. Meanwhile, quality of governance, financial development and political globalisation encouraged FDI Inflows in Lower Middle-Income countries. In addition, this study also found a significant moderating effect of financial development on three factors i) Quality of governance, ii) Political globalisation, and iii) Social globalisation in the Upper Middle-Income Countries. However, for the Lower Middle-Income region, a significant moderating effect of financial development was found only on two factors i) Political globalisation, and ii) Social globalisation. The study suggests that policymakers in Upper & Lower Middle-Income countries should improve quality of governance and encourage the political and social globalisation to stimulate FDI Inflows.